Current-driven coherent skyrmion generation - DEĞER, CANER; YAVUZ, İLHAN (NATURE PUBLISHING GROUP, 2019)
The next-generation logic and memory devices using magnetic skyrmions as spintronic information carriers are frequently studied, thanks to their remarkable magnetic stability, extremely compact size and very-low-cost driving forces within nanotracks. In order to realize skyrmion-based spintronic devices, understanding the skyrmion generation and their dynamics are essential. In this study, we have carried out a systematic micromagnetic simulation study on coherent magnetic skyrmion generation in which we theoretically engineered nanotracks by embedding an anti-notch to a channel of certain width. We found that the drift velocity and the skyrmion generation frequency can be tailored by the applied spin-polarized DC current density. Moreover, skyrmion generation is crucially affected by both damping and nonadiabaticity parameters, as well as the geometry of the anti-notch. We anticipate that our predictions provide rational basis for skyrmion-based devices in which skyrmions are used as information carriers, and influence future discussions.
Keywords: MAGNETIC SKYRMIONS; LATTICE